Professional Identity Formation in a Liberal Israeli Rabbinical Seminary Spiritual Transformers in the Learned Curriculum - Muszkat-Barkan, Michal; Rosenstein, Marc (2018)
We examined Israeli Reform rabbis' reflections on what components of their training most influenced the development of their rabbinical identity. Theoretical perspectives applied in planning the study and analyzing the data were: professional identity formation; pedagogies of training clergy; and taught vs. learned curriculum. We identified four common learning experiences as important in rabbinical identity formation: introspection; gaining ownership of classical texts; partner/group study; and teachers who were mentors/models. We argue that these 'spiritual transformers' express a search by the rabbinical students for a sense of connectedness, with themselves, with each other, and with the tradition and its bearers.